Pulmonary oxygen uptake and muscle deoxygenation kinetics during heavy intensity cycling exercise in patients with emphysema and idiopathic pulmonary fibrosis. Issue 1 (December 2017) - McNarry, Melitta; Harrison, Nicholas; Withers, Tom; Chinnappa, Narendra; Lewis, Michael
Abstract Background Little is known about the mechanistic basis for the exercise intolerance characteristic of patients with respiratory disease; a lack of clearly defined, distinct patient groups limits interpretation of many studies. The purpose of this pilot study was to investigate the pulmonary oxygen uptake ( V . .V O2 ) response, and its potential determinants, in patients with emphysema and idiopathic pulmonary fibrosis (IPF). Methods Following a ramp incremental test for the determination of peak V . .V O2 and the gas exchange threshold, six emphysema (66 ± 7 years; FEV1, 36 ± 16%), five IPF (65 ± 12 years; FEV1, 82 ± 11%) and ten healthy control participants (63 ± 6 years) completed three repeat, heavy-intensity exercise transitions on a cycle ergometer. Throughout each transition, pulmonary gas exchange, heart rate and muscle deoxygenation ([HHb], patients only) were assessed continuously and subsequently modelled using a mono-exponential with ( V . .V O2, [HHb]) or without (HR) a time delay. Results The V . .V O2 phase II time-constant (τ) did not differ between IPF and emphysema, with both groups significantly slower than healthy controls (Emphysema, 65 ± 11; IPF, 69 ± 7; Control, 31 ± 7 s;P < 0.05). The HR τ was slower in emphysema relative to IPF, with both groups significantly slower than controls (Emphysema, 87 ± 19; IPF, 119 ± 20; Control, 58 ± 11 s;P < 0.05). In contrast, neither the [HHb] τ nor [HHb]:O2 ratio differed between patient groups. Conclusions The slower V . .V O2 kinetics in emphysema and IPF may reflect poorer matching of O2 delivery-to-utilisation. Our findings extend our understanding of the exercise dysfunction in patients with respiratory disease and may help to inform the development of appropriately targeted rehabilitation strategies.